2(2)-3y=6(2)+2(2)

Simple and best practice solution for 2(2)-3y=6(2)+2(2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2)-3y=6(2)+2(2) equation:



2(2)-3y=6(2)+2(2)
We move all terms to the left:
2(2)-3y-(6(2)+2(2))=0
We add all the numbers together, and all the variables
-3y+22-84=0
We add all the numbers together, and all the variables
-3y-62=0
We move all terms containing y to the left, all other terms to the right
-3y=62
y=62/-3
y=-20+2/3

See similar equations:

| 13a-8a=10 | | 11j^2+43j-4=0 | | X(x+5)=2x(x+1) | | 16=4q-8 | | 6v^2-22v+12=0 | | 0.5x-1=0.25x+2.5 | | 20q^2+16q-36=0 | | 9u^2+46u+5=0 | | 6x-91+2x+53=180 | | s-68=11s=79 | | 17.5=7xx= | | 21(s+22)=945 | | 3x+10=15+2x | | 18(b+28)=900 | | 14=13x | | 3x+10+15+2x=360 | | t/31+975=990 | | 236+x=1.204 | | y/7=-32 | | (x-1)(x^2-5x-3)=0 | | 2n+62/3=19 | | y+y=-4y+8 | | 4(x-5)+6x=x+3)10-5 | | 1/2d=1/4 | | 22=n+-12 | | 4v2+7v-22=-7 | | 3(x+3)-14=7(x-1)+4 | | 12(y•y)+40y-7=0 | | 2x-(x-1)=12 | | 2.0x-10=4 | | 4/5t-1.4=6/10 | | y=-3/3 |

Equations solver categories